Language Poetty in Class VIII Student Discussions of SMPIT Ash Shiddiqiyyah, South Tangerang - Khoirunnisa, Putri; Triswati, Meutia; Coutas, Penelope (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to describe the deviation and compliance of the politeness of language principles that occur in class discussion activities in class VIII students of SMPIT Ash Shiddiqiyyah South Tangerang in terms of word selection and polite manner of discussion. Methodology: The method used in the study Analysis of the Utilization of Principles of Language politeness in the Discussion Activities of Class VIII Students of SMPIT Ash Shiddiqiyyah South Tangerang is a qualitative descriptive method. The technique used in collecting data uses the technique of referring skillful engagements, recording techniques, and note-taking techniques. Main Findings: The results of the study on class VIII SMPIT Ash Shiddiqiyyah South Tangerang showed that the number of violations of language politeness violations that occurred in class discussion activities were greater than their compliance. The principle of politeness that is often violated is the maxim of generosity, humility and approval. As for those who do not appear in speech in class VIII are the maxims of wisdom, the maxim of acceptance and the maxim of conclusions. Novelty/Originality of this study: This research offers a new view regarding language politeness in discussions of class VIII students at SMPIT Ash Shiddiqiyyah Tangsel by considering the specific cultural context and school environment. Previously, studies related to language politeness were often carried out in general contexts without paying attention to the unique nuances and characteristics of each educational environment.